Anglican Identities: Logos Idealism, Imperial Witness, Commonweal Ecumenism. By Garry Dorrien. Waco: Baylor University Press, 2024. xiii + 642 pp. 59.99 paperback - Heaney, Robert Stewart (Church history, 2025)
Anglican Identities: Logos Idealism, Imperial Witness, Commonweal Ecumenism. By Garry Dorrien. Waco: Baylor University Press, 2024. xiii + 642 pp. 59.99 paperback. - Volume 94 Issue 2